Grounding context in face processing: color, emotion, and gender - Gil, Sandrine; Le Bigot, Ludovic (Frontiers in Psychology, 2015)
In recent years, researchers have become interested in the way that the affective quality of contextual information transfers to a perceived target. We therefore examined the effect of a red (versus green, mixed red/green and achromatic) background–known to be valenced−on the processing of stimuli that play a key role in human interactions, namely facial expressions. We also examined whether the valenced-color effect can be modulated by gender, which is also known to be valenced. Female and male adult participants performed a categorization task of facial expressions of emotion in which the faces of female and male posers expressing two ambiguous emotions (i.e., neutral and surprise) were presented against the four different colored backgrounds. Additionally, this task was completed by collecting subjective ratings for each colored background in the form of five semantic differential scales corresponding to both discrete and dimensional perspectives of emotion. We found that the red background resulted in more negative face perception than the green background, whether the poser was female or male. However, whereas this valenced-color effect was the only effect for female posers, for male posers, the effect was modulated by both the nature of the ambiguous emotion and the decoder’s gender. Overall, our findings offer evidence that color and gender have a common valence-based dimension.